Revision of the genus Metallesthes Kraatz and description of Metallesthes anneliesae, a new species of Cetoniinae (Coleoptera: Scarabaeidae) from Queensland and New South Wales, Australia - Moeseneder, Christian H.; Hutchinson, Paul M.; Lambkin, Christine L. (Zootaxa, 2014)
The endemic Australian flower chafer genus Metallesthes Kraatz, 1880 (Coleoptera: Scarabaeidae: Cetoniinae) is revised. Metallesthes anneliesae Moeseneder & Hutchinson new species is described from southern Queensland and New South Wales. Metallesthes unicolor (Macleay, 1863) revised status is raised from synonymy with Metallesthes metallescens (White, 1859). Metallesthes metallescens and Metallesthes unicolor are redescribed and their holotypes are figured. A specimen bearing a Nonfried type label is designated as the lectotype of Metallesthes subpilosa Nonfried, 1891. Metallesthes subpilosa new synonymy is synonymised with Pseudoclithria ruficornis (Westwood, 1874). A key to the species of the genus is provided. Distribution maps are shown and known host plants are listed.